2021
DOI: 10.1177/08862605211021962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Online Heterosexist Experiences on Physical and Mental Health in Sexual Minorities: An Examination of the Cognitive and Affective Mechanisms

Abstract: Cyber violence has emerged as a new source of minority stress over the past decade. Due to the anonymous and unrestrictive nature of the internet, cyber violence is even more blatant and pervasive than in person violence for sexual minority individuals. The present study aimed to examine whether and how online and offline experiences of heterosexism are related to physical and mental health. A total of 941 sexual minority individuals participated in a community-based online survey study. The findings indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Majority of the participants identified as lesbian or gay (72.6%), followed by bisexual or pansexual (21.0%), and questioning, queer, asexual, or other (6.4%). The distribution of sexual orientation in the current sample was comparable to that of previous studies of sexual minorities in Hong Kong (Chan, 2021; Suen et al, 2020). Around 63.9% reported community college or university as their highest level of education, followed by secondary school or below (19.2%), and master’s degree or above (16.9%).…”
Section: Methodssupporting
confidence: 86%
“…Majority of the participants identified as lesbian or gay (72.6%), followed by bisexual or pansexual (21.0%), and questioning, queer, asexual, or other (6.4%). The distribution of sexual orientation in the current sample was comparable to that of previous studies of sexual minorities in Hong Kong (Chan, 2021; Suen et al, 2020). Around 63.9% reported community college or university as their highest level of education, followed by secondary school or below (19.2%), and master’s degree or above (16.9%).…”
Section: Methodssupporting
confidence: 86%
“…The themes included general physical health, self-harm, digestion, physical and sexual violence, and fear during physical health exams (pap smears, breast exams, misdiagnoses, etc.). Studies frequently found harmful effects on health caused by stigma either through qualitative calculations or qualitative collections on the state of participants' physical health or experiences with healthcare appointments (Chan, 2022;English et al, 2022;Ghabrial, 2017;Gyamerah et al, 2020;Dsouza et al, 2023;Logie et al, 2019;Milner & McNally, 2020;Paine, 2021;Wolfe et al, 2022). The most common theme was stigma causing anxiety among LGBTQ+ individuals, which led them to avoid healthcare and tend to their health concerns (this theme will be mirrored in the healthcare services findings as well, proving to be significant with regards to LGBTQ+ health conditions).…”
Section: Physical Healthmentioning
confidence: 99%
“…Sexuality discrimination was included in 17 articles. Data ranged from simply acknowledging the discrimination that participants faced (Bogart et al, 2020;DiGuiseppi et al, 2022;Ghabrial, 2017;Gyamerah et al, 2020;Malta et al, 2020), sexual orientation stigma negatively impacting LGBTQ+ relationships through anticipated rejection, adverse provider reaction, heteronormative care (Chan, 2022;Milner & McNally, 2020;Logie et al, 2019;Schwab et al, 2024;, and findings suggested that nongay or non-cisgender LGBTQ+ people experienced more significant stigma (Powers, 2021;Ronzón-Tirado et al, 2022). Other studies found that anti-LGBTQ+ stigma increased self-stigma (Ching et al, 2022) and a lack of group cohesion among rural LGBTQ+ individuals while facing more significant stigma for their sexuality (Scott, 2022).…”
Section: Sexuality Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have suggested that perceived parental attitudes towards marriage, endorsement of filial piety, and the valence of parent‐child relationships might subject Chinese sexual minority people to pressure and identity struggles (Bie & Tang, 2016; Hu & Wang, 2013; Huang et al., 2020; Shao et al., 2018; Sun, Budge, et al., 2020). Although the current generation of Chinese SMYP in Hong Kong and Taiwan have grown up in a relatively accepting environment (Kong, 2019), recent studies show that diverse forms of rejection and victimisation against SMYP remain pervasive in these regions (Chan, 2021; Li et al., 2020). Psychosocial interventions to protect Chinese SMYP's mental health are needed.…”
Section: Introductionmentioning
confidence: 99%